2020
DOI: 10.1155/2020/4105382
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide as a Potential Alternative for the Treatment of Myocardial Fibrosis

Abstract: Harmful, stressful conditions or events in the cardiovascular system result in cellular damage, inflammation, and fibrosis. Currently, there is no targeted therapy for myocardial fibrosis, which is highly associated with a large number of cardiovascular diseases and can lead to fatal heart failure. Hydrogen sulfide (H2S) is an endogenous gasotransmitter similar to nitric oxide and carbon monoxide. H2S is involved in the suppression of oxidative stress, inflammation, and cellular death in the cardiovascular sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 161 publications
(188 reference statements)
0
25
0
2
Order By: Relevance
“…Recent interest has been addressed to the role of H 2 S in the field of mesenchymal stem cells (MSCs), so the use of H 2 S donors has been proposed to treat various pathological situations such as osteoporosis, immune disorders, inflammation and cardiovascular disease [17][18][19][20][21]. However, some H 2 S donors' adverse effects were evidenced in different cell types [10][11][12], therefore, for the safe therapeutic use of these molecules, it is necessary to consider first that very different effects could depend on the context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent interest has been addressed to the role of H 2 S in the field of mesenchymal stem cells (MSCs), so the use of H 2 S donors has been proposed to treat various pathological situations such as osteoporosis, immune disorders, inflammation and cardiovascular disease [17][18][19][20][21]. However, some H 2 S donors' adverse effects were evidenced in different cell types [10][11][12], therefore, for the safe therapeutic use of these molecules, it is necessary to consider first that very different effects could depend on the context.…”
Section: Discussionmentioning
confidence: 99%
“…In pathological models, the treatment with H₂S donors could increase the proliferation and survival of MSCs attenuating hypoxia-induced apoptosis by enhancing the antiapoptotic gene expression [ 18 , 19 ]. Moreover, it has also been reported that H₂S improved the survival of transplanted MSCs into infarcted myocardium in a rat model [ 20 ] and exerted an antifibrosis role in cardiovascular disease [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S markedly prevented the development of cardiac fibrosis and decreased the collagen content in the cardiac tissue by inhibiting the activity of intracardiac angiotensin II (Huang et al, 2012). In addition, the suppression of inflammation, the reduction of cardiac apoptosis from oxidative stress and improving mitochondrial derangements are likely to have antifibrotic roles under hypertensive conditions (Wang et al, 2011;Kang et al, 2020). Antihypertensive effects of H 2 S, via modulation of channel activities and the cGMP/PKG pathways, may also contribute to the suppression of fibrosis caused by hypertension (Meng et al, 2015).…”
Section: Oral Sts Improves Systolic Function and Cardiac Remodelingmentioning
confidence: 99%
“…Cardiovascular magnetic resonance (CMR) imaging has emerged as a novel, non-invasive diagnostic tool to assess myocardial fibrosis (11), a key pathological process in HF (12). The importance of myocardial fibrosis to predict the prognosis in different cohorts of patients had been reported (13); however, there are limited clinical data on the interaction between insulin resistance and myocardial fibrosis in patients with HF.…”
Section: Introductionmentioning
confidence: 99%